Michel Foucault and the teaching of Physics: sidewalks - Ferreira, Marcello (Pesquisa e Debate em Educação, 2018)
Michel Foucault is undoubtedly one of the most important and consecrated thinkers of all time, especially for his contributions against order. His work has unique characteristics, either by its conceptions and its methods, or by the way of approaching, in historical-philosophical perspectives, foundational themes of social life. This article seeks to present and problematize Foucault’s theoretical perspectives, especially in the domains of knowledge, power and ethics, articulating them with possible fields of research and practices in physics teaching. We do not propose a method or a manual for the application of Foucault in themes of research/teaching in physics. However, a new way of looking is proposed, necessary for a new way of teaching.